Endoscopic Endonasal Resection of C1–C2 Pannus, a Step-by-Step Surgical and Anatomical Description: 2-Dimensional Operative Video - Elhammady, Mohamed Samy; Al-Bar, Mohammad; Roser, Florian (Journal of Neurological Surgery Part B: Skull Base, 2020)
Expanded endonasal endoscopic approaches provide access to the entire central skull base and craiocervical junction. The authors present a case of an 81-year-old man who presented with progressive spastic quadriparesis to the point of being wheel-chair bound. Cervical spine computed tomography (CT) and magnetic resonance imaging (MRI) demonstrated multilevel extensive spondylitic changes with a large pannus at the C1–2 junction, severely compressing the spinal cord (Figs. 1 and 2). Given the significant anterior spinal cord compression and the patient's substantial weakness, the decision was made to perform an endoscopic endonasal anterior cervical decompression and resection of the pannus followed a posterior cervical fusion. The patient recovered well following surgery with significant improvement of motor function. The preoperative assessment, the step-by-step surgical technique, and the technical nuances are demonstrated and discussed.The link to the video can be found at: https://youtu.be/HzrZO-0Vol4.
Keywords: craniocervical junction; expanded endoscopic endonasal approach; C1–C2 pannus; craniocervical decompression